2006
DOI: 10.1111/j.1530-0277.2006.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Neuropeptide Y in the Central Nucleus of the Amygdala Decreases Ethanol Self‐administration in “Anxious” Rats

Abstract: These results suggest that virally mediated alterations in NPY levels in the CeA differentially affect ethanol consumption in rats with low and high basal levels of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 53 publications
2
67
1
Order By: Relevance
“…These involve reward, pleasure, or choice and can override the hypothalamic homeostatic control pathways. Indeed, the intake of specific nutrients, including carbohydrates, fats, and alcohol can be affected by neuropeptide activity within the amygdala (3,4,36,47,48,55). The amygdala system is also well connected to other areas of the brain through numerous projections from and toward the cortex, other areas of the limbic system, areas of the hypothalamus or the brain stem (39).…”
Section: Discussionmentioning
confidence: 99%
“…These involve reward, pleasure, or choice and can override the hypothalamic homeostatic control pathways. Indeed, the intake of specific nutrients, including carbohydrates, fats, and alcohol can be affected by neuropeptide activity within the amygdala (3,4,36,47,48,55). The amygdala system is also well connected to other areas of the brain through numerous projections from and toward the cortex, other areas of the limbic system, areas of the hypothalamus or the brain stem (39).…”
Section: Discussionmentioning
confidence: 99%
“…Also, increases in amygdalar NPY expression suppress excessive drinking associated with repeated cycles of ethanol liquiddiet access and periods of abstinence in Wistar rats (Thorsell et al, 2007). Injection into the CeA of a viral vector encoding prepro-NPY selectively reduces ethanol drinking by Long Evans rats determined to be "anxious" based on behavior in an elevated plus maze (Primeaux et al 2006). Finally, Pandey and coworkers (2005) showed that infusion of NPY (100 pmol) into the CeA reduced ethanol drinking in P rats with continuous access to ethanol solution.…”
Section: Discussionmentioning
confidence: 99%
“…Viral vector-induced increases in amygdalar NPY expression blunt excessive drinking associated with repeated cycles of ethanol liquid-diet access and periods of abstinence in Wistar rats (Thorsell et al, 2007). Injection into the CeA of a viral vector encoding prepro-NPY reduces continuous access-ethanol drinking by "anxious," but not "nonanxious" Long Evans rats, divided based on behavior in an elevated plus maze (Primeaux et al 2006). Finally, P rats with a brief history of ethanol selfadministration consume less ethanol following NPY infusion into the CeA, and also following increases in NPY activity in the CeA produced via alterations in cAMP-responsive elementbinding protein (CREB) function (Pandey et al 2005).…”
mentioning
confidence: 99%
“…NPY microinjection into the CeA suppresses alcohol consumption in alcohol-dependent and abstinent P rats (Gilpin et al 2008a,b), and also in rats showing innately high anxietylike behavior (Primeaux et al 2006 (Sajdyk et al 2002) in anxiety-like behavior. Mouse studies indicate that Y 1 Rs mediate the suppressive effects of NPY on alcohol drinking (Thiele et al 2002;Sparta et al 2004;Eva et al 2006).…”
Section: Neuropeptide Y (Npy) and Alcohol-related Behaviormentioning
confidence: 99%